MAINTANENCE OF THE STYLISTIC PRAGMATIC ASPECT IN THE TRANSLATION OF POPULAR SCIENTIFIC TEXTS FROM MODERN MAGAZINES (A CASE STUDY OF TEXTS FROM THE ECONOMIST AND SCIENTIFIC AMERICAN) - L. R. Vartanova (Гуманитарные и юридические исследования)
The article reviews ways of maintaining the pragmatic aspect of stylistic means in the process of translating popular scientific texts from English into Russian. The material for the study were articles from modern English-language publications The Economist and Scientific American. The article focuses on the role of popular scientific texts in contemporary linguistic discourse and provides an analysis of the translation techniques used in the translation of the selected texts.Works of I. S. Alekseeva, I. V. Arnold, V. N. Komissarov, S. V. Tyulenev, etc. on the translation studies theory served the theoretic and methodological basis of the study.Preliminary linguostylistic analysis of the texts revealed the following most productive means of expression: epithet, metaphor, comparison. The analysis also revealed a large number of idioms and other stylistic means, which allow to maintain a captivating narration in the popular scientific article. In most cases, the translation of the selected lexical units required a complex transformation using the following methods of translation: addition, omission, meaning exchange, replacement, and others. Currently, popular scientific texts are in high demand among readers, which makes the problem of translating such texts into a target language a topical issue in the modern translation discourse.